Focal Bronchiectasis Causing Abnormal Pulmonary Radioiodine Uptake in a Patient with Well-Differentiated Papillary Thyroid Carcinoma. (11th October 2012) - Gargya, Ash; Chua, Elizabeth
Abstract : Background . False-positive pulmonary radioactive iodine uptake in the followup of differentiated thyroid carcinoma has been reported in patients with certain respiratory conditions. Patient Findings . We describe a case of well-differentiated papillary thyroid carcinoma treated by total thyroidectomy and radioiodine ablation therapy. Postablation radioiodine whole body scan and subsequent diagnostic radioiodine whole body scans have shown persistent uptake in the left hemithorax despite an undetectable stimulated serum thyroglobulin in the absence of interfering thyroglobulin antibodies. Contrast-enhanced chest computed tomography has confirmed that the abnormal pulmonary radioiodine uptake correlates with focal bronchiectasis. Summary . Bronchiectasis can cause abnormal chest radioactive iodine uptake in the followup of differentiated thyroid carcinoma. Conclusions . Recognition of potential false-positive chest radioactive iodine uptake, simulating pulmonary metastases, is needed to avoid unnecessary exposure to further radiation from repeated therapeutic doses of radioactive iodine.